2016
DOI: 10.1016/j.atmosenv.2016.04.035
|View full text |Cite
|
Sign up to set email alerts
|

On-road measurement of NH3 and N2O emissions from a Euro V heavy-duty vehicle

Abstract: a b s t r a c tThe use of selective catalytic reduction systems (SCR) to abate NOx vehicular emissions brings new concerns on the emissions of the byproducts NH 3 and N 2 O. Therefore, NH 3 and N 2 O on-road emissions from a Euro V truck equipped with a SCR were measured in real time using a QCL-IR. Results bring to light possibility to perform this kind of real time measurements for other pollutants besides, hydrocarbons, NOx, CO and CO 2 . The capability to measure NH 3 and N 2 O in a second-by-second basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 7 publications
0
15
1
1
Order By: Relevance
“…The MEXA 1400 QL-NX has a wavelength resolution close to 0.006 cm − 1 . Further details on the instrument and its performance during the real time measurements of NH 3 emission on transient cycles and correlation between this instrument and a FTIR can be found in Suarez-Bertoa et al, 2015 , Suarez-Bertoa et al, 2016 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MEXA 1400 QL-NX has a wavelength resolution close to 0.006 cm − 1 . Further details on the instrument and its performance during the real time measurements of NH 3 emission on transient cycles and correlation between this instrument and a FTIR can be found in Suarez-Bertoa et al, 2015 , Suarez-Bertoa et al, 2016 .…”
Section: Methodsmentioning
confidence: 99%
“…NH 3 (which is a precursor of fine particle formation in the atmosphere ( Kim et al, 2000 ; Phan et al, 2013 )) and N 2 O (which is a powerful greenhouse gas and the single most important ozone-depleting substance (ODS) ( Ravishankara et al, 2009 )) are present in HDV exhaust due the use of urea/SCR DeNO x systems (i.e., NOx reduction systems) ( Guan et al, 2014 ). It has recently been proved possible to measure these emissions on-road ( Suarez-Bertoa et al, 2016 ) opening the door for this type of measurement to be considered in further regulation revisions. While NH 3 emissions from vehicles are only regulated in EU and Korea ( EU, 2011 , MOE, 2014 ), N 2 O emission standards have recently been introduced by the U.S. Environmental Protection Agency (EPA) under the Clean Air Act ( EPA, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fontaras et al (2012) [11] tested one Euro V diesel truck with PEMS in the city of Milan and found that NO x exceeded the emission limit by four times over normal work conditions, while HC and PM levels were found within limits. Bertoa et al (2016) [12] tested a Euro V HDV with Selective Catalytic Reduction (SCR) after-treatment also using PEMS, under different driving conditions with a large share of urban operation, and found that NO x emissions exceeded the respective Euro limit by four times. Thus, despite the evolution and the increasing stringency of the emission standards during the years and the use of more efficient after-treatment systems, vehicles exhibit NO x levels higher than the corresponding limits when driven in real-world conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, we explored the possibility of their measurement using laboratory grade instrumentation during on-road operation. In previous studies we showed that it is possible to measure NH 3 and N 2 O emissions from heavy-duty and light-commercial vehicles during on-road operation using laboratory grade quantum cascade laser detectors (QCL-IR) and Fourier Transform InfraRed spectroscopy (FTIR) [33][34][35]. We also showed that during on-road operation a gasoline passenger car and a series of CNG light-commercial vehicles present substantial emissions of NH 3 and diesel vehicles equipped with SCR presented low NH 3 emissions [20,24].…”
mentioning
confidence: 99%